Pushing the Line: Teaching Suburban Seventh Graders to be Critically Conscious through Historical Inquiry and Civic Letter-Writing - Beutel, Andy (Radical Teacher, 2018)
Engaging in critical teaching with non-marginalized suburban middle school students is both challenging and necessary in the Age of Trumpism. In this paper, I explain the constraints on critical educators teaching in an affluent, suburban public school setting as well as the possibilities for working within this system to increase students’ critical consciousness. In the inquiry-based learning project I describe, I combine critical pedagogy theory with historical literacy pedagogy in order to enable seventh grade students in a world history course to critique current problems in the United States under Trump through the comparative analysis of different historical and modern sources and action-based letter-writing to the president. I include an overview an explanation of the school setting and culture, a rationale for and summary of the lessons within the inquiry project, a description of the class discussions, and excerpts from students’ letters and reflections revealing their thinking.